2016
DOI: 10.1073/pnas.1511509113
|View full text |Cite
|
Sign up to set email alerts
|

Response of single bacterial cells to stress gives rise to complex history dependence at the population level

Abstract: Most bacteria live in ever-changing environments where periods of stress are common. One fundamental question is whether individual bacterial cells have an increased tolerance to stress if they recently have been exposed to lower levels of the same stressor. To address this question, we worked with the bacterium Caulobacter crescentus and asked whether exposure to a moderate concentration of sodium chloride would affect survival during later exposure to a higher concentration. We found that the effects measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 34 publications
0
64
1
Order By: Relevance
“…More broadly, mechanisms of memory and history dependence in bacterial systems are being uncovered to better understand the dynamics of bacterial survival and adaptation in changing environments [69][70][71]. For example, a recent study showed that the survival of Caulobacter crescentus in response to a high concentration of sodium chloride stress depended on the duration and timing of an earlier treatment of a moderate concentration of sodium chloride and that this effect was linked to delays in cell division, which led to cell-cycle synchronization [72]. Another study described what they call response memory, which is when a gene regulatory network continues to persist after the removal of its external inducer.…”
Section: Discussionmentioning
confidence: 99%
“…More broadly, mechanisms of memory and history dependence in bacterial systems are being uncovered to better understand the dynamics of bacterial survival and adaptation in changing environments [69][70][71]. For example, a recent study showed that the survival of Caulobacter crescentus in response to a high concentration of sodium chloride stress depended on the duration and timing of an earlier treatment of a moderate concentration of sodium chloride and that this effect was linked to delays in cell division, which led to cell-cycle synchronization [72]. Another study described what they call response memory, which is when a gene regulatory network continues to persist after the removal of its external inducer.…”
Section: Discussionmentioning
confidence: 99%
“…"Memory" of stress responses has been reported for different aspects of cellular adaptations to stress conditions (38)(39)(40). The timing of growth resumption from stationary phase has been discovered to correlate with the timing of entry into stationary phase, although the molecular mechanism of this phenomenon has not been elucidated (40).…”
Section: Discussionmentioning
confidence: 99%
“…In a similar approach Mathis et al also traced the Caulobacter cell history by live cell imaging in microfluidic devices after salt stress to monitor the history-dependence of bacterial stress responses. [20] They observed the emergence of memorylike behaviour at the level of the population, indicating that past events can indeed modulate the behavioural traits of individuals and groups of bacteria.…”
Section: Virologymentioning
confidence: 99%